Establishing robust infection control at a new hospital: the AIIMS Rajkot experience - Padhi, Abhishek; Bhise, Mayuri; Chaudhary, Anil; Vyas, Radha; Talwar, Vidhi; Agarwal, Ashwini; Katoch, CDS (International Journal of Infection Control, 2025)
The establishment of robust infection control practices is crucial in any new healthcare facility to ensure patient safety and prevent healthcare-associated infections (HAIs). All India Institute of Medical Sciences (AIIMS) Rajkot, a newly inaugurated medical institution in Western India, faced the significant challenge of implementing these practices from the ground up, beginning with its Outpatient Department services initiation on 31 December 2021. The AIIMS Rajkot initiated its infection control program by forming a Hospital Infection Control Committee and appointing dedicated Infection Control Officers and Infection Control Nurses. This initiative was supported by comprehensive training programs, the implementation of advanced infection control measures such as bundle care, HAI surveillance, and the development of outbreak investigation teams. Furthermore, the hospital focused on the continuous improvement of these practices through routine audits and the use of a digital Infection Control Risk Assessment form. The institution successfully integrated a structured infection control framework that includes rigorous training sessions, the implementation of a Hospital Infection Control Manual, and the establishment of a robust needle stick injury management team. These measures have led to improved compliance with infection prevention protocols, as evidenced by hand hygiene audits and reduced incidence of HAIs. The journey of establishing infection control practices at AIIMS Rajkot highlights the importance of a structured approach in new healthcare settings. The successful integration of these practices not only enhances patient and staff safety but also sets a standard for future healthcare facilities. The AIIMS Rajkot’s proactive measures and continuous improvement efforts serve as a model for effectively addressing the challenges of infection control in a dynamic healthcare environment.